Autonomous and adaptive beaconing strategy for multi‐interfaced wireless mobile nodes. Issue 12 (1st October 2015) - Tahar, Rafaa; Dhraief, Amine; Belghith, Abdelfettah; Mathkour, Hassan; Braham, Rafik
Abstract: Ad hoc wireless communications rely on beaconing to manage and maintain several network operations and to share relevant network parameters among network nodes. Beacon frames are sent at the start of each beacon interval. The frequency of beaconing depends on whether beacon intervals are fixed size or may be adapted and regulated according to the perceived network and workload conditions. On the other hand, current mobile nodes usually embed several heterogeneous wireless interfaces that urge the design of an adaptive beaconing strategy. In this paper, we propose an autonomous and adaptive beaconing strategy for multi‐interfaced mobile wireless nodes that is capable of regulating the beacon interval size dynamically according to the perceived network conditions. The proposed strategy is based on a joint dynamic estimation of both the announcement traffic indication message (ATIM) window and the beyond‐ATIM window sizes for each beacon interval. Extensive simulations were conducted using OMNeT++ to ascertain the improvements achieved by autonomously regulating the entire beacon interval to take into account the network and workload conditions. Obtained results showed that the two proposed approaches improve significantly the efficiency of the network in terms of throughput, end‐to‐end delay, and power consumption. The proposed fixed beacon interval (fixed‐BI) approach stands as an enhanced version of the power‐saving multi‐channel MAC protocol (PSM‐MMAC). The proposed variable beacon interval (variable‐BI) approach, which regulates dynamically both of the ATIM and the beyond‐ATIM windows, outperforms both the fixed‐BI and the PSM‐MMAC. In particular, under nominal traffic loads, the end‐to‐end delay of the variable‐BI is much lower than those provided by the fixed‐BI and PSM‐MMAC. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The use of an adaptive and autonomic strategy for multi‐interfaced wireless nodes to dynamically regulate the beacon interval improves the overall network performance.